Pengaruh Financial Leverage Terhadap Perataan Laba Dimoderasi Firm Size Di Perbankan Indonesia - Devi, Heidy Paramitha (IAIN Surakarta, 2019)
One of the steps that can be taken to reduce earnings fluctuations is income smoothing, by moving high income in a certain year into an unfavorable period, this is done to create a stable company profit so that it is reflected in good company performance in the eyes of investors. The purpose of this study is to determine whether company size is able to moderate the effect of financial leverage on income smoothing. This research was conducted at companies listed in the 2013-2017 banking period. The number of samples in this study were 110 samples that were selected using the purposive sampling method. The data analysis technique used in this study is logistic regression analysis. The results of this study indicate that financial leverage has no effect on income smoothing, and company size is not able to moderate the effect of financial leverage on income smoothing. Keywords: Income Smoothing, Financial leverage, Company Size, Banking Sector JEL Classification:G21, G32, L25, M41